Potential of Thaumatococcus danielli (Benn) for poverty reduction in Osun state, Nigeria (2005)
This study examined the economic value Of market margins of Thaumatococcus danielli and its potentials for poverty reduction in Osun State. Five Local Government Areas (LGAs): Odo-Otin, Boripe, Iwo, Irewole and Atakumosa, were randomly sampled from the 30 LGAs in the state. A total of 150 structured questionnaires were administered to randomly selected farmers/harvesters, marketers and users of the plant. Descriptive statistics and economic analysis were used to analyze the data. The results show that virtually all the farmers were collectors rather than cultivators, harvesting the wild Thaumatococcus danielli either from the forest or cocoa plantations. However 66% of the farmers were willing to plant Thaumatococcus. Analysis of gender distribution of harvesters and marketers show that 86% of the harvesters were males while all the marketers were females. The average rate of returns on investment of 55.88 ±2.58% far exceeds the maximum commercial bank lending rate of 19.4%. In order to harness the potential contribution of Thaumatococcus to poverty reduction, farmers should be educated about its economic potentials and be provided with agronomic information and advice.